Familial aggregation to S. japonicum infection in a defined area of the village Macanip, Jaro, Leyte, Philippines - Siao, Rosebelle May Y. (2000)
Familial aggregation to S. japonicum infection was assessed together with known risk factors to the disease, which may act as confounders or interact with specific genetic mechanism in causing disease among susceptible individuals.A cross-sectional study design was utilized, with 46 index subjects and 129 relatives of index subjects included in the data analysis. All the subjects were residents for the years 1994-1995 of the study site, which was a defined area in the village Macanip of Jaro, Leyte. Only one index subject was taken for each household, chosen among the offspring of the household head. The first-degree relatives of the index subject, composed of the parents, siblings and offspring, were then identified and taken into the study. Individuals excluded from the study were those who submitted less than 3 stool samples and did not receive praziquantel treatment or were not ascertained to be disease-free prior to the start of the study.Two statistical approaches were utilized to deal with the lack of independence in the data. The first approacj was bootstrapping after logistic regression was performed. The second approach was random effects modeling. Both these approaches yielded evidence of familial aggregation to S. japonicum infection even after controlling for the effects of significant covariates such as age and water contact. Relatives of infected index subjects were seen to be at higher risk to S. japonicum infection than relatives of uninfected index subjects, raising the great possibility that susceptibility to infection is also genetically regulated.This study can be viewed as a springboard for more sophisticated genetic researches. The conduct of studies dealing with segregation analyses and those dealing with genetic markers are recommended to further test the possibility that susceptibility to s. japonicum infection is also genetically regulated.